2015 IEEE International Conference on Communication Workshop (ICCW) 2015
DOI: 10.1109/iccw.2015.7247345
|View full text |Cite
|
Sign up to set email alerts
|

Effective RF codebook design and channel estimation for millimeter wave communication systems

Abstract: Millimeter wave (mmWave) technologies can enable current mobile communication systems to achieve higher data rates. However, wireless channels at mmWave frequencies experience higher isotropic path loss. Therefore, employing a suitable beamforming algorithm is an indispensable element of any mmWave system. Traditional multiple-input multipleoutput (MIMO) systems employ digital beamforming where each antenna element is equipped with one RF chain. In case of mmWave systems, however, the power consumption, signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…In order to design hybrid beamformers, however, it is required to solve a complex nonconvex optimization problem due to the constant modulus constraint imposed by the phase shifters [3]. In addition, the phase shifters in practical systems have discrete resolution which converts the optimization to a computationally expensive combinatorial problem [8], [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to design hybrid beamformers, however, it is required to solve a complex nonconvex optimization problem due to the constant modulus constraint imposed by the phase shifters [3]. In addition, the phase shifters in practical systems have discrete resolution which converts the optimization to a computationally expensive combinatorial problem [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the hybrid beamforming approach, it has been shown that the baseband precoder and the RF beamformer can be designed either jointly [8]- [10] or in two stages [11]- [15]. For a point-to-point system, a joint design approach based on matching pursuit was proposed when the channel is sparse [8], [9]. In this method, firstly the singular vectors of the channel should be calculated, and then the hybrid beamformer is derived by solving an optimization problem to minimize the Euclidean distance between the matrices containing the singular vectors and the weights of the hybrid beamformer.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that our method provides almost the same performance as [12] which has higher complexity as multiple computations of SVD and inversions of matrices with larger dimension than K × K are required. In addition to observing a good match between the simulations and closed-forms in (5), (9) and (11), Fig. 2 shows that the proposed phase shifter selection based structures effectively reduce the number of the active phase shifters while providing a comparable performance to that of the subconnected structures with N active phase shifters.…”
Section: Simulation Resultsmentioning
confidence: 58%
“…Under perfect CSI and uncorrelated Rayleigh fading assumption, Fig. 2 presents the spectral efficiency achieved by simulations and the closed-forms in (5), (9) and (11) for N = 256, K = 4, β = 75% and S = 4. It is noted that β = 75% and S = 4 are equivalent to having only KL = N/4 = 64 active phase shifters.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For instance, [27] elaborates on the performance of scheduling in the return-link of a multi-beam satellite system. Moreover, [28] uses a genetic algorithm to achieve a nearoptimal array gain in all directions during codebook-based beamforming.…”
Section: Literature Reviewmentioning
confidence: 99%